2021
DOI: 10.1001/jamanetworkopen.2021.24324
|View full text |Cite
|
Sign up to set email alerts
|

Association of Timing and Duration of Prenatal Analgesic Opioid Exposure With Attention-Deficit/Hyperactivity Disorder in Children

Abstract: Key Points Question Is prenatal analgesic opioid exposure associated with attention-deficit/hyperactivity disorder (ADHD) in children? Findings In this cohort study of 73 480 children, with a mean follow-up of 11 years, no association between timing of analgesic opioid exposure during pregnancy and ADHD was found. The risk of ADHD diagnosis was elevated after exposure to opioids for 5 or more weeks compared with exposure for 4 weeks or less. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 57 publications
(114 reference statements)
0
13
0
Order By: Relevance
“…While a few studies indicate increased risks for educational delay, lower IQ, and poor language performance in children with POE, other studies show no significant differences in cognitive outcomes (63)(64)(65)(66)(67). There is, however, greater evidence to suggest an increased risk of poor long-term behavioral outcomes in children with POE, including difficulties with executive functioning (67), attention deficit hyperactivity disorder (ADHD) (68,69) and autism spectrum disorders (ASD) (70,71). Children with POE and a history of NOWS are shown to be more likely to have poor neurodevelopmental consequences including lower IQ, poor educational testing performance, lower attention, meet disability criteria, and require additional classroom therapies and services when compared to children with POE who did not develop NOWS, or healthy controls (18,(71)(72)(73)(74).…”
Section: Discussionmentioning
confidence: 99%
“…While a few studies indicate increased risks for educational delay, lower IQ, and poor language performance in children with POE, other studies show no significant differences in cognitive outcomes (63)(64)(65)(66)(67). There is, however, greater evidence to suggest an increased risk of poor long-term behavioral outcomes in children with POE, including difficulties with executive functioning (67), attention deficit hyperactivity disorder (ADHD) (68,69) and autism spectrum disorders (ASD) (70,71). Children with POE and a history of NOWS are shown to be more likely to have poor neurodevelopmental consequences including lower IQ, poor educational testing performance, lower attention, meet disability criteria, and require additional classroom therapies and services when compared to children with POE who did not develop NOWS, or healthy controls (18,(71)(72)(73)(74).…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies 10 , 11 suggested that longer prenatal opioid analgesic exposures were associated with adverse neurodevelopmental outcomes. In the present study, we found that prenatal opioid analgesic exposures in two to three 4-week intervals were associated with low literacy and numeracy scores (wβ, −0.19; 95% CI, −0.35 to −0 04).…”
Section: Discussionmentioning
confidence: 99%
“…However, mothers who reported use during 2 or more 4-week periods are more likely to have consumed a higher total dose. 11 The MoBa participation rate was 41%; thus, our cohort had a potential self-selection bias of the healthiest women. 63 , 64 When interpreting our results, one should keep in mind that the generalizability may be limited to families that are above average in socioeconomic resources.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations